Effects of PGPR microbial inoculants on the growth and soil properties of Avena sativa, Medicago sativa, and Cucumis sativus seedlings - Li, Haiyun; Qiu, Yizhi; Yao, Tuo; Ma, Yachun; Zhang, Huirong; Yang, Xiaolei (Soil & tillage research, 2020)
•We have established PGPR microbial inoculants containing four compatible PGPR strains.•PGPR microbial inoculants had abilities of fix nitrogen, solubilize phosphorus, secrete IAA, and act as biocontrol agents.•PGPR microbial inoculants promoted the growth of Avena sativa, Medicago sativa, and Cucumis sativus seedlings.•PGPR microbial inoculants increased enzyme activity and available nutrient content in the soil. Plant growth promoting rhizobacteria (PGPR) are an important bacterial resource for microbial fertilizers, which can promote plant growth and increase crop yields. In this study, multifunctional PGPR microbial inoculants with the ability to fix nitrogen, solubilize phosphate, secrete indole-3-acetic acid (IAA) and exhibit biological control were generated. These PGPR microbial inoculants contained four compatible strains of Providencia rettgeri P2, Advenella incenata P4, Acinetobacter calcoaceticus P19, and Serratia plymuthica P35. All four strains had the ability to solubilize inorganic and organic phosphate, and fix nitrogen. In addition, strains P2 and P4 had the ability to secrete IAA, and strain P35 exhibited inhibition of Helminthosporium tritici-vulgaris, Alternaria solani, Fusarium oxysporum, and Sclerotinias clerotiorum. The effects of the PGPR microbial inoculants on the growth, physiology, and soil properties of oat (Avena sativa), alfalfa (Medicago sativa), and cucumber (Cucumis sativus) seedlings were verified by a pot experiment. The PGPR microbial inoculants increased the dry weight (DW), plant height (PH), root length (RL), root average diameter (RAD), root surface area (RSA), root volume (RV), and chlorophyll content (PCH) of A. sativa, M. sativa, and C. sativus seedlings, and enhanced the activity of peroxidase (POD), catalase (CAT), and superoxide dismutase (SOD) in the seedlings. Furthermore, PGPR microbial inoculants increased soil urease (SURE), invertase (SIN), alkaline phosphatase (SAKP), catalase (SCAT) activity, available nitrogen (AN), available phosphorus (AP), available potassium (AK), and organic carbon (SOC) in the rhizosphere of A. sativa, M. sativa, and C. sativus. In summary, our results showed that the PGPR microbial inoculants had a promoting effect on A. sativa, M. sativa, and C. sativus seedlings by increasing soil enzyme activity and available nutrient content. These PGPR microbial inoculants can be used as an alternative method of environmentally friendly biocontrol of plant disease or to improve crop systems.